Regesten Kaiser Friedrichs III. (1440-1493) Die Urkunden und Briefe des Österreichischen Staatsarchives in Wien (1470-1475) - Luger, Daniel (2012)
As a result of the death of Duke Charles the Bold of Burgundy and the marriage of his only daughter Mary to Maximilian, the heir of Emperor Frederick III, the economically and culturally prospering lands of Flanders and Brabant became hereditary possessions of the Habsburgs. With this, the foundations for the Habsburgs's hegemony were laid. This dynastic project was for about 10 years (1467-1477) in the spotlight of Emperor Frederick's III diplomatic efforts and that with mixed results. Many documents regarding those negotiations are preserved in the Habsburg "Hausarchiv", now the "Haus-, Hof- und Staatsarchiv" in Vienna. Documents only up to the year 1469 have been published in the "Regesta Imperii - Regesten Friedrichs III." so far. Therefore, in the present publication the systematic collection and registration of charters as well as letters of this important emperor is continued up to the year 1475. As a fundamental edition of sources this publication provides a basis for further research questions concerning the late Middle Ages. The presented material serves as a foundation for studies of political communication in the late Middle Ages, e.g. the relationship between Emperor Frederick III and Duke Charles of Burgundy. The material can provide a basis for a study of the differences and similarities of the diplomacy of two differently developed cultural spheres in the late Middle Ages. Additionally, the formal and compositional analyses of diplomatic writings provide information about the various media of diplomatic communication, the objectives, possibilities and success of diplomatic efforts. An investigation of the actors occurring in these areas can reveal the institutional structure, which enabled the development of networks of aristocratic, civic and legally trained elites. Another basic topic of the provided documents is Emperor Frederick's III territorial activity especially in the years 1470 to 1473, when the emperor primarily stayed in his hereditary lands. There he was faced with areas of conflict clearly represented in the sources. Frederick's definition of his role as the head of the Habsburg house is illustrated by his diplomatic relationship to his cousin Sigmund. Among many other topics, also Frederick's role as the supreme judge of the empire becomes evident in the present sources, especially by judicial summons and judgments of the "Kammergericht" (supreme court), which was pledged to Archbishop Adolf of Mainz at that time.